2016
DOI: 10.1039/c6ra12023g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of ruthenium-fullerides

Abstract: We report a simple and original procedure for preparing Ru–C60 polymeric chains, which spontaneously self-assemble as polymeric spherical particles, and can be surface decorated with Ru nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 77 publications
(98 reference statements)
1
35
0
Order By: Relevance
“…The reaction was allowed to react overnight at -20°C and the last TEM analysis performed showed that the size of the nanospheres remained similar, 255.7 ± 39.5 nm; while the Rh NP on the surface presented a bimodal distribution, 2.4 ± 0.7 and 4.7 ± 0.4 nm, and isolated NP were no longer observed. These observations make feasible to propose that, as previously observed during the synthesis of Ru-C60 compounds, 30 the nanospheres are composed by molecular species, which form this particular shape due to the stirring and the different viscosity between the assynthesized species and the solvent. 40 Figure S3).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…The reaction was allowed to react overnight at -20°C and the last TEM analysis performed showed that the size of the nanospheres remained similar, 255.7 ± 39.5 nm; while the Rh NP on the surface presented a bimodal distribution, 2.4 ± 0.7 and 4.7 ± 0.4 nm, and isolated NP were no longer observed. These observations make feasible to propose that, as previously observed during the synthesis of Ru-C60 compounds, 30 the nanospheres are composed by molecular species, which form this particular shape due to the stirring and the different viscosity between the assynthesized species and the solvent. 40 Figure S3).…”
Section: Resultssupporting
confidence: 63%
“…These species are structurally similar to the ruthenium nanocatalysts stabilized with fullerene C60 described in a previous study by some of us. 30 In this abovementioned work, the decomposition under dihydrogen of [Ru(COD)(COT)] in the presence of fullerene C60 provided Ru based catalyst composed by Ru-C60 molecular spheres with the surface decorated with Ru NP; as pointed out by a combination of characterization techniques including TEM, WAXS, Extended X-Ray Absorption Fine Structure (EXAFS), and supported by DFT calculations. Also, Ru-C60 fulleride nanospheres synthesised in DCB displayed a size of 200.0 ± 38.5 nm , which is similar to the ones of Rh-C60 materials.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the Ni/Ni distance within the polymer chains was found to be slightly longer (11.230(6)Å at 280 K) than the Pd/Pd distances. Recently, 1-D C 60 Ru polymeric chains were theoretically studied by Leng et al 55 using periodic DFT calculations. According to their calculations, the most stable polymer is that with Ru atoms in a h 2(6) -h 6 Fig.…”
Section: Methodsmentioning
confidence: 99%